COMPLICATED AS AN ARTISTIC ALTERNATIVE ARCHETYPE OF DESTINY (BASED ON THE NOVEL OF T. PROKHAS’KO “COMPLICATED”) - Tkachyk, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the research for mythical and poetical base of the image of “Complicated” and its refraction through the prism of the author world-view of Taras Prokhas’ko. The archetype of the fate that makes the post-modernist text an integrated whole as a feasible scenario of life-story is analyzed.